Tablas de amortización y análisis de la variación de las tasas de interés por los métodos francés y alemán. - Vivero Aguirre, Olga Maritza (My University, 2017)
El presente trabajo está orientado a las personas que necesitan realizar un crédito en las diferentes entidades financieras que existen en nuestro medio y desconocen la importancia de conocer cuáles son los beneficios que se obtienen al realizar un crédito de consumo con la tasa de interés efectiva más baja del mercado y en cuanto a las tablas de amortización tener conocimiento previo de cuál de los dos métodos es el que más conviene, ya que al momento de realizar un crédito se desconoce sobre estos y para lo cual he dado a conocer la diferencia de cada uno de ellos aplicando las tablas de amortización por los métodos Francés y Alemán los cuales hemos podido ver la diferencia a aplicarlo en el ejercicio planteado para que las personas tengan una visión más amplia en cuanto al pago de los respectivos intereses los cuales debe cancelar por el dinero prestado el cual vendría a ser un capital que el cliente va a invertir y a obtener una rentabilidad.
This work is aimed at people who need to perform a credit in different financial institutions that exist in our environment and are unaware of the importance of knowing what are the benefits that are obtained by performing a credit of consumption with the effective interest rate lower market and in terms of amortization tables have foreknowledge of which of the two methods is which suits. Since at the time of a credit is unknown about these and for which. I have given to knowing the difference of each one of them applying the tables of depreciation methods French al German which we have been able to see the difference to apply it in the proposed exercise so that people have a broader view as to the respective interest payments which must cancel by borrowed money which would come to be an capital that customer is going to invest and achieve profitability. Should be noted that the French system of depreciation is one of the systems most used banking characteristics since the amortization of the capital serves consecutively, the payment of the capital is increased and the payment of interests in a decreasing way. Likewise the German system of depreciation is the most used for mortgage loans since their fees are fixed and capital is amortized constant and interests are diminishing.
Keywords: ENTIDADES FINANCIERAS; TASA; INTERÉS; AMORTIZACIÓN; CRÉDITO; CAPITAL; RENTABILIDAD